Locomotor and anti-immobility effects of buprenorphine in combination with the opioid receptor modulator samidorphan in rats. (1st March 2019) - Burke, Nikita N.; Ferdousi, Mehnaz; Deaver, Daniel R.; Finn, David P.; Roche, Michelle; Kelly, John P.
Abstract: Modulation of the opioid system has re-emerged as a potential therapeutic avenue for treating depression, with efficacy of a fixed-dose combination of buprenorphine (BUP), a partial μ-opioid receptor (MOR) agonist and κ-opioid receptor (KOR) antagonist, and samidorphan (SAM), a potent MOR antagonist, as an adjuvant treatment in patients with major depressive disorder (MDD). To advance understanding of the mechanism of action underlying this combination, we examined BUP, SAM and their combination in a series of rat behavioural assays. We examined effects on locomotor activity in Sprague Dawley (SD) rats over an extended period of time in a home-cage tracking system, and behavioural despair (immobility) in the forced swim test (FST), a commonly-used test to study antidepressants, in SD and Wistar-Kyoto (WKY) rats. Strain differences in opioid receptor and prepropeptide mRNA expression in the brain (prefrontal cortex, amygdala, hippocampus and striatum) were examined using qRT-PCR. BUP produced locomotor hyperactivity in SD rats from 2 to 6 h following administration, which was attenuated by SAM. In SD rats, a low, but not a high, dose of SAM in combination with BUP counteracted swim-stress induced immobility. This effect was not seen with BUP alone. In contrast, BUP alone reduced immobility in WKY rats, and this effect was enhanced by a low, but not high, dose of SAM. In WKY rats, MOR mRNA expression was higher in the hippocampus and lower in the striatum vs. SD rats. KOR mRNA expression was higher in the amygdala and nociceptin receptor (NOP) mRNA expression was lower in the hippocampus vs. SD rats. Differences in opioid receptor expression may account for the differential behavioural profile of WKY and SD rats. In summary, administration of BUP, a MOR receptor agonist together with a MOR opioid-receptor antagonist, SAM, reduces behavioural despair in animal models traditionally used to study effects of antidepressants. Highlights: The combination of buprenorphine and samidorphan counteract swim-stress induced immobility in two rat strains. Wistar Kyoto rats exhibit altered opioid receptor gene expression in discrete brain regions compared to Sprague Dawley rats. Pharmacological opioid modulation reduces behavioural despair in animal models commonly used to evaluate antidepressants.